XIX ӘСИР ДИДАКТИКАЛЫҚ ЛИРИКАСЫНЫҢ ИЗЕРТЛЕНИЎИ - Орынбаев, Т.Б. (FAN va JAMIYAT, 2021)
The article examines the state of study of didactic lyrics in the Karakalpak literature of the XIX century. This problem is considered in the article on the basis of the research of the literary scientist K.Turdibaev.